Emergence of quantum confinement in topological kagome superconductor CsV3Sb5 - Yongqing Cai; Yuan Wang; Zhanyang Hao; Yixuan Liu; Xuelei Sui; Zuowei Liang; Xiao-Ming Ma; Fayuan Zhang; Zecheng Shen; Chengcheng Zhang; Zhicheng Jiang; Yichen Yang; et al. (Communications Materials, 2024)
Abstract Quantum confinement is a restriction on the motion of electrons in a material to specific region, resulting in discrete energy levels rather than continuous energy bands. In certain materials, quantum confinement could dramatically reshape the electronic structure and properties of the surface with respect to the bulk. Here, in the recently discovered kagome superconductors CsV3Sb5, we unveil the dominant role of quantum confinement in determining their surface electronic structure. Combining angle-resolved photoemission spectroscopy (ARPES) measurement and density-functional theory simulation, we report the observations of two-dimensional quantum well states due to the confinement of bulk electron pocket and Dirac cone to the nearly isolated surface layer. The theoretical calculations on the slab model also suggest that the ARPES observed spectra are almost entirely contributed by the top two layers. Our results not only explain the disagreement of band structures between the recent experiments and calculations, but also suggest an equally important role played by quantum confinement, together with strong correlation and band topology, in shaping the electronic properties of this material.